Small Bragg‐plane slope errors revealed in synthetic diamond crystals. (26th October 2020) - Pradhan, Paresh; Wojcik, Michael; Huang, Xianrong; Kasman, Elina; Assoufid, Lahsen; Anton, Jayson; Shu, Deming; Terentyev, Sergey; Blank, Vladimir; Kim, Kwang-Je; Shvyd'ko, Yuri
Abstract : X‐ray rocking curve imaging is used to study the smallest achievable Bragg‐plane slope errors in the best presently available synthetic diamond crystals and how they compare with those of perfect silicon crystals Abstract : Wavefront‐preserving X‐ray diamond crystal optics are essential for numerous applications in X‐ray science. Perfect crystals with flat Bragg planes are a prerequisite for wavefront preservation in Bragg diffraction. However, this condition is difficult to realize in practice because of inevitable crystal imperfections. Here, X‐ray rocking curve imaging is used to study the smallest achievable Bragg‐plane slope errors in the best presently available synthetic diamond crystals and how they compare with those of perfect silicon crystals. It is shown that the smallest specific slope errors in the best diamond crystals are about 0.08 (3) µrad mm −2 . These errors are only 50% larger than the 0.05 (2) µrad mm −2 specific slope errors measured in perfect silicon crystals. High‐temperature annealing at 1450°C of almost flawless diamond crystals reduces the slope errors very close to those of silicon. Further investigations are in progress to establish the wavefront‐preservation properties of these crystals.